Implementasi Sistem Akuntansi Berbasis Microsoft Access pada UMKM Blue Wash - Iskandar Itan; Alvina Alvina (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
This community service program aims to assist Blue Wash MSME in improving the quality of its financial record-keeping through the implementation of a Microsoft Access-based accounting system. Blue Wash MSME, which operates in the laundry service sector, currently relies on simple bookkeeping methods using Microsoft Excel. This practice has resulted in unstructured transaction records and difficulties in obtaining accurate financial information. The program employed a qualitative approach involving interviews and direct observation of the business partner to identify accounting-related issues faced by the business partner. Based on the identified needs, an accounting information system was designed and developed to support systematic financial recording. The system features master data management, purchase and sales transaction processing, general journal recording, inventory management, and automated financial reporting. The resulting accounting system is expected to improve the effectiveness and efficiency of financial management at Blue Wash MSME and support more structured and accountable financial reporting in compliance with applicable accounting standards.